Revision of the Taft-Hartley Act - Slichter, Sumner H. (Quarterly Journal of Economics, 1953)
I. Introduction, 149. — II. Protection of the right of employees to organize, 150. — III. Protection of employers against unfair labor practices by unions, 158. — IV. Safeguarding the relations of individual workmen with unions, 160. — V. Protection of the rights of neutrals in industrial disputes, 164. — VI. Effect of the Act on the influence of Communists in unions, 167. — VII. Provisions designed to protect the country against disputes that imperil national health or safety, 168. — VIII. Miscellaneous provisions of the Act, 170. — IX. Effects of the Act on the growth of union membership, the spread of union security, and the number of damage suits brought against unions, 172. — X. Principal changes needed in the Taft-Hartley Act, 174. — XI. Some concluding observations, 179.